A NEW RECORD FOR NITIDULIDAE FAUNA OF TURKEY: SORONIA PUNCTATISSIMA (ILLIGER, 1794) (COLEOPTERA: NITIDULIDAE) - Özgen, İnanç; Topdemir, Aykut (My University, 2020)
In this study; a widespread nitidulid species Soronia punctatissima (Illiger, 1794) is reported for the first time from Turkey.)
Keywords: Entomoloji